HEGEMONI DALAM NOVEL RONGGENG DUKUH PARUK KARYA AHMAD TOHARI - Wahana, Dajora Nebulla (sarasvati, 2019)
A literary work was an image of community social from a condition that is written and adds to it when once with an element of fiction. The social condition referred to include the structure, the system, of the people come from historical, including also the form of the hegemony of conducted by individuals or groups in those societies. This study aims to described the form of the hegemony of conducted by the main figure in the, srinthil, against other figures in a novel ronggeng dukuh paruk and the cause of the problem. The kind of research that is used is qualitative descriptive by using the hegemony of the theory. Research conducted in this research taken from the novel ronggeng dukuh paruk the work of ahmad tohari. The data collection using a technique been listening to and techniques recorded everything. While, data was undertaken analysis cycles reduction-analyze data-conclusion. The result of from the study states that found the form of and the causes of the hegemony of the principal character in a novel ronggeng dukuh paruk. The form of the hegemony of that leads to the stronghold of pharaoh matter.